Cultural Narratives of Micronesian Islander Parent Leaders: Maternal and Children's Health, the School System, and the Role of Culture - Connie Kim Yen Nguyen-Truong; Jacqueline Leung; Kapiolani Micky (JMIR Publications, 2020)
Background: In Oregon in the United States' Pacific Northwest, Native Hawaiians/Pacific Islanders including Micronesian Islanders (MI) substantially grew by 68%; however, research is sparse. This is often due to data aggregation as Asian and Pacific Islanders and community members' reluctance and wariness to participate in research due to a history of unethical research in the Pacific. The MI community experienced miscarriages, stillbirths, and intellectual and developmental disabilities. Organizational MI community leaders expressed a need to explore the voices of MI parent leaders (MIPLs). The purpose of the community-based participatory qualitative descriptive pilot study was to explore the perceptions and experiences of MIPLs with maternal and children's health, the school system, and the influence of culture. Methods: A trained MI community health worker recruited eight MIPLs from an urban area of the Pacific northwest in the United States. A group level assessment included illustrative storytelling and is a participant-driven qualitative method that guided data collection and analysis with real-time involvement with MIPL. The discussions lasted for 90 minutes. MIPL shared stories by writing and drawing pictures onto the flip chart papers, transcribed main points, and analyzed the data with researchers. Researchers recorded field notes of the interactions. Researchers debriefed with MIPL to assure trustworthiness and credibility of the findings. Findings: MIPL are Compact of Free Association citizens. Their age ranged from 26 to 42 years, have lived in the United States an average of 12.63 years, and most reported having less than $15,000 total household income before taxes. Four main themes were identified: MI cultural identity, English language and MI culture disharmony, zero or delayed prenatal care, and uncertainty for the future of MI children who have disabilities or developmentally delayed as they progress through the school system. Conclusion: Health care providers including nurses and school officials need to have a culturally specific understanding of the MI community and must consider their needs, culture, and language barriers.